A systematic review on the effectiveness of anti-doping education for university students - Adam R. Nicholls; Lambros Lazuras; Michael Petrou; Ornella Corazza; Carlos Santos; António Júlio Nunes; Michał Rynkowski; João F. Martins; Thomas Zandonai; Uta Kühn; Łukasz Tota (Emerging Trends in Drugs, Addictions, and Health)
Background: Doping poses a threat to the integrity of sport and the health of athletes who dope, including university students. In this systematic review, we identified the content of anti-doping education that universities provide, the disciplines mainly targeted by such education (e.g., sports science, medicine, physiotherapy, etc.), and the effectiveness of anti-doping education on university students’ anti-doping knowledge, attitudes, and other related constructs. Method: We systematically searched the literature using nine different search engines, manually searched relevant journals, and used pearl growing. Results: This review included four studies comprising 1,410 university students. The content of the education programmes varied, although information about prohibited substances and rules was included in all interventions. Two studies targeted a specific cohort of students (e.g., medical and sports science students), whereas the other two recruited university students without specifying the subject discipline. All intervention programmes had a positive impact on doping knowledge, two studies had a positive effect on anti-doping attitudes, and one study impacted morality. Conclusions: These four studies are essential, but methodological limitations mean that better-designed education interventions for university students are required. Researchers could assess the effectiveness of education interventions on anti-doping knowledge and key psycho-social variables among this population.